Transforming the experience of illness into action – Patient and spouses experiences of involvement in a patient and family advisory council. Issue 6 (June 2021) - Missel, Malene; Hansen, Malene Haugaard; Petersson, Nadja Buch; Forman, Jacqueline; Højskov, Ida Elisabeth; Borregaard, Britt
Highlights: A Patient and Family Advisory Council is a specific way of conducting organisational patient engagement. By participating in the Council, the participants feel a genuine engagement and interest from the health care professionals. . Patient and Family Advisory Council is also a way of increasing the process of recovery by sharing narratives with others in a similar position. The Council is also a way of increasing the process of recovery by sharing narratives with others in a similar position. Abstract: Objective: The objective was to explore patients' and spouses' perception and attitudes towards participating in a patient and family advisory council. Methods: A qualitative study with interviews conducted within a phenomenological-hermeneutical frame, inspired by Ricoeur were conducted with current and former participants (patients and/or spouses) of a patient and family advisory council in Denmark. Results: In total, 16 participants were interviewed (12 former patients/four spouses) with a mean age of 68 (range 49–79) and 44 % women. After the analysis, perceptions and attitudes towards participating in a patient advisory council emerged in four themes; "Payback", "A personal invitation", "A safe and equal atmosphere", and "Sharing, caring, and healing". Conclusion: Participants of an advisory council express a need for "paying it back" to the health care system. When being part of the advisory council, the participants expressed feeling a genuine engagement and interest from the health-care professionals – leading to a feeling of being equal and taken seriously. The advisory council increased the process of recovery by sharing narratives with peers. Practical value: Experiences of being part of an advisory council lead to an understanding of "why" former patients and spouses participate. This knowledge can help others to recruit members.